A Test of the Three-Step Theory of Suicide among Chinese People: A Study Based on the Ideation-to-Action Framework. Issue 4 (2nd October 2019) - Yang, Li; Liu, Xinchun; Chen, Wei; Li, Ling
Abstract : The aim of this study was to test the Three-Step Theory (3ST) of suicide in a sample of college students in China (N = 1, 097). All participants completed a battery of questionnaires indexing psychological pain, hopelessness, connectedness, suicide capacity, suicide ideation, and suicide attempt. The prevalence of suicide ideation and suicide attempt among the sample were 21.42% and 3.83%, respectively. The hierarchical regression analysis showed that psychological pain and hopelessness interacted to predict suicide ideation, and that connectedness was the most protective against ideation in those high on both pain and hopelessness. Suicide capacity differentiated attempters from ideators above and beyond current suicide ideation. These findings provide preliminary evidence for the validity of 3ST of suicide within Chinese contexts. Implications for suicide prevention and intervention and future research directions are also discussed.